The Relationship Between Work-Life Balance And Job Satisfaction Among Correctional Officers In Ternate City - Afrizal Muhram Embisa; Abdul Hamid (Information Technology and Science (ITScience), 2026)
The high job demands placed on correctional officers can disrupt the equilibrium between their professional and personal lives, thereby impacting their job satisfaction. This study aims to determine the relationship between work-life balance and job satisfaction among correctional officers at the Ternate City Correctional Institution. A quantitative approach with a correlational method was employed, involving 90 officers selected through purposive sampling. Data analysis was conducted using Spearman’s rho correlation test. The results demonstrated a positive and significant relationship between work-life balance and job satisfaction, with a correlation coefficient of 0.479 and a significance value of 0.000 (p < 0.05). These findings indicate that higher work-life balance among officers is associated with greater job satisfaction. Consequently, work-life balance serves as a crucial factor in enhancing officers' job satisfaction.